Review: Bioaccumulation of heavy metals in fish and other aquatic organisms from Karachi Coast, Pakistan - Ramzy Yousif; MUHAMMAD IQBAL CHOUDHARY; SHAKEL AHMED; QURATULAN AHMED (Nusantara Bioscience, 2021)
Abstract. Yousif RA, Choudhary MI, Ahmed S, Ahmed Q. 2021. Review: Bioaccumulation of heavy metals in fish and other aquatic organisms from Karachi Coast, Pakistan. Nusantara Bioscience 13: 74-85. Heavy metals are being utilized in a variety of ways in industries, agriculture, food processing and household in many forms. Metals are unique environmental and industrial pollutants in the sense that they are neither created nor destroyed by human beings but are only transported and transformed into various products. The present study deals with the findings of various investigators on the effect of heavy metals on fish and other aquatic organisms on Karachi coasts of Pakistan. The polluted areas (Rivers and Karachi coasts) receiving effluents from industrial, agricultural, municipal and domestic wastes. The order of abundance of the metals were as fellow; Fe > Zn > Cu > Mn > Cd > Pb > Cr > Ni > Hg > As. Most studies showed that essential metals (Fe, Zn, Cu, and Mn) in aquatic organisms are much high, but the quantities of non-essential metals are found to be less. This review has shown that fish and other aquatic organisms are used as bio-monitoring species in heavy metal pollution. It is suggested that such investigations should be continuous in terms of both human health and determination of metal pollution in aquatic environment.